Efeito do tempo de austenitização na evolução da microestrutura e comportamento mecânico dos aços inoxidáveis UNS S42000 e UNS S41003 - Alves, Renata Rodrigues (2023)
Quenching is one of the most common methods of heat treatment and aims to increase the mechanical strength of the material by transforming austenite into martensite at high temperatures, followed by rapid cooling. The formation of martensite depends on various factors, such as the time the material is held at the austenitization temperature. In the context presented and with the aim of contributing to a better understanding of the microstructure evolution and mechanical behavior of stainless steels with different carbon contents, this study aimed to investigate the effect of austenitization time followed by quenching treatment. The materials studied were low carbon steel, commercially known as UNS S41003 or 410D, and medium carbon steel, commercially known as UNS S42000 or 420A. Two heat treatment conditions were studied, in the first one, the steels were austenitized at 1000 ℃ with varying austenitization time (5 min, 30 min, 60 min, 120 min, and 240 min) and then quenched in water, while in the second condition, the samples were annealed at 800 ℃ and then austenitized at 1000 ℃ with varying austenitization time (5 min, 30 min, 60 min, 120 min, and 240 min), and finally quenched in water. Thermodynamic simulations were performed using Matcalc software to evaluate the relative stability of phases and precipitates under equilibrium conditions. It was observed that both steels would be austenitized at 1000 ℃, and the carbides dissolved, however, it was identified that the carbide dissolution depends on the austenitization time when outside of equilibrium. Despite the low carbon content, austenitization of the 410D steel was possible due to the presence of austenitizing elements such as Ni, Mn, and N, thus, both steels showed a martensitic structure after the water quenching process. It was possible to observe that with an increase in austenitization time, the martensite lath increased due to the gradual increase in grain size. The distribution of the prior austenitic grain size was found to be heterogeneous for longer times, related to the dissolution of carbides. In addition to presenting a similar microstructural evolution, both steels also exhibited similar mechanical behavior, with the material softening as the grain size increased, associated with the freer dislocation movement with increasing austenitization time. Finally, the obtained data on prior austenitic grain size and hardness were treated with a 95% confidence level. It is believed that the results of this study provide a foundation for a better understanding of the austenitization time parameter in the heat treatment of stainless steels.